Wire Ropes Tension, Endurance, Reliability - Feyrer, Klaus; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
The main goal of this book is to present the methods used to calculate the most important parameters for ropes, and to explain how they are applied on the basis of numerous sample calculations. The book, based on the most important chapters of the German book DRAHTSEILE, has been updated to reflect the latest developments, with the new edition especially focusing on computational methods for wire ropes. Many new calculations and examples have also been added to facilitate the dimensioning and calculation of mechanical characteristics of wire ropes. This book offers a valuable resource for all those working with wire ropes, including construction engineers, operators and supervisors of machines and installations involving wire ropes.
Wire Ropes, Elements and Definitions -- Wire Ropes under Tensile Load -- Wire Ropes Under Bending and Tensile Stresses.
Keywords: Engineering; Machinery; Civil engineering; Metals; Engineering; Machinery and Machine Elements; Metallic Materials; Civil Engineering; Electronic books